The relationship between Glocal advertising value and brand awareness, associations by mediating customer attitude - Elsetouhi, Ahmed; Ebeid, Ahmed Yehia; Tolba, Yasmin (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines how glocal advertising value and customer attitudes toward advertising influence brand awareness and brand associations among international brand customers in Egypt. It is the first to investigate these constructs in a collectivist, high power distance, and uncertainty-avoidant cultural context. Data from 415 customers were analyzed using structural equation modeling (SEM) with AMOS 22. Unlike prior studies relying on content analysis, this research evaluates glocal advertising via consumers’ perceived value dimensions: entertainment, informativeness, credibility, and irritation. Results show that glocal advertising value significantly enhances customer attitudes, which in turn positively influence brand awareness and brand associations. Customer attitudes also mediate the relationship between advertising value and brand outcomes. Specifically, entertainment, informativeness, and credibility strengthen perceived value, while irritation reduces it. The study concludes that glocal advertising tailored to cultural contexts strengthens brand equity directly and indirectly through customer attitudes. Campaigns such as Orange Egypt’s Ramadan advertisement illustrate how cultural adaptation fosters positive consumer responses and enduring brand associations. Advertisers should create entertaining, informative, and credible messages while minimizing irritation. Collaboration with local agencies ensures cultural relevance, and combining global standardization with local adaptation improves effectiveness. Post-campaign surveys are recommended to capture customer feedback and refine future strategies.